Honey dressing on a leg ulcer with tendon exposure in a patient with type 2 diabetes. (16th November 2018) - Teobaldi, Ilaria; Stoico, Vincenzo; Perrone, Fabrizia; Bruti, Massimiliano; Bonora, Enzo; Mantovani, Alessandro
Summary: Honey has been used as a wound dressing for hundreds of years by ancient civilizations, but only recently it has acquired scientific interest because of its relevant biological properties. In the last decade, indeed, several trials and observational studies have reported that, compared to conventional treatment (e.g. antiseptics, polyurethane film, paraffin gauze, soframycin-impregnated gauze), honey dressings seem to be better in healing time of different types of wounds, including diabetic foot ulcers. However, to date, information about a potential favorable biological effect of honey dressings on diabetic ulcers with exposed tendon are still scarce. Notably, foot or leg ulcers with exposed tendon are serious complications in patients with type 2 diabetes, as they are associated with an increased risk of adverse outcome. Therefore, the use of effective and safe treatments to bring these lesions to timely healing is very important in clinical practice. We herein report the case of a Caucasian adult patient with type 2 diabetes presenting a chronic right posterior lower limb ulcer (Texas University Classification (TUC) 2D) with tendon exposure that was successfully treated with honey dressings (glucose oxidase (GOX) positive with peroxide activity) in addition to systemic antibiotic therapy, surgical toilette and skin graft. In our case, the use of honey dressing for treating exposed tendon tissue probably allowed the timely wound healing. Although further studies are required, such treatment may constitute part of the comprehensive management of diabetic wounds, including those with tendon exposure, and should be considered by clinicians in clinical practice. Learning points: Honey has been used as a wound dressing for hundreds of years, but only recently it has acquired scientific interest for its biological properties. Several studies have documented that, compared to conventional dressings, honey seems to be better in healing time of different types of wounds, including diabetic foot ulcers. Our case report is the first to highlight the importance to use honey dressings also for the treatment of ulcers with tendon exposure in patients with type 2 diabetes, suggesting that this kind of dressing should be considered by clinicians in clinical practice.